Comparisons in the Recovery Response From Resistance Exercise Between Young and Middle-Aged Men. Issue 12 (December 2017) - Gordon, Joseph A.; Hoffman, Jay R.; Arroyo, Eliott; Varanoske, Alyssa N.; Coker, Nicholas A.; Gepner, Yftach; Wells, Adam J.; Stout, Jeffrey R.; Fukuda, David H.
Abstract : Abstract: Gordon, JA III, Hoffman, JR, Arroyo, E, Varanoske, AN, Coker, NA, Gepner, Y, Wells, AJ, Stout, JR, and Fukuda, DH. Comparisons in the recovery response from resistance exercise between young and middle-aged men. J Strength Cond Res 31(12): 3454–3462, 2017—The purpose of this study was to compare the effects of a bout of high-volume isokinetic resistance exercise protocol (HVP) on lower-body strength and markers of inflammation and muscle damage during recovery between young and middle-aged adult men. Nineteen recreationally trained men were classified as either a young adult (YA: 21.8 ± 2.0 years; 90.7 ± 11.6 kg) or a middle-aged adult (MA: 47.0 ± 4.4 years; 96.0 ± 21.5 kg) group. The HVP consisted of 8 sets of 10 repetitions, with 1 minute of rest between each set, performed on an isokinetic dynamometer at 60°·s −1 . Maximal voluntary isometric contractions and isokinetic peak torque (PKT) and average torque (AVGT) (measured at 240° and 60°·s −1, respectively) were assessed at baseline (BL), immediately post (IP), 120 minutes, 24, and 48 hours after HVP. Blood was obtained at BL, IP, 30, 60, 120 minute, 24, and 48 hours after HVP to assess muscle damage and inflammation. All performance data were analyzed using repeated measures analysis of covariance, whereas all inflammatory and muscle damage markers were analyzed using a 2-way (time × group) repeated measures analysis of variance. Results revealed no between-group differences for PKT, AVGT, or rate of torque development at 200 ms (RTD200). No between-group differences in myoglobin, creatine kinase, C-reactive protein, or interleukin-6 were observed. Although BL differences in muscle performance were observed between YA and MA, no between-group differences were noted in performance recovery measures from high-volume isokinetic exercise in recreationally trained men. These results also indicate that the inflammatory and muscle damage response from high-volume isokinetic exercise is similar between recreationally trained, young, and middle-aged adult men.